2009
DOI: 10.1159/000199722
|View full text |Cite
|
Sign up to set email alerts
|

Association of Apolipoproteins with Symptoms of Asthma and Atopy among Schoolchildren

Abstract: Background: There is evidence for an association between serum cholesterol concentrations and asthma, but little is known about the underlying mechanisms. We explored the associations between serum apolipoprotein concentrations and symptoms of asthma and atopy. Methods: In a population-based cross-sectional study among 10-year-old schoolchildren (n = 462), plasma concentrations of apolipoprotein AI (apoAI) and apolipoprotein B (apoB) were measured. Information on disease symptoms and diagnoses was collected by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 83 publications
(79 reference statements)
0
12
0
Order By: Relevance
“…For example, apolipoproteins were found to be over-expressed in the milk of allergic mothers. Like protease inhibitors, apolipoproteins have been previously linked to asthma and atopy in children [ 28 ]; and more recently, their mimetic peptides have emerged as a potential new treatment for asthma [ 29 ]. Furthermore, our study provides also novel proteins that are different between allergic and non-allergic mothers, like transthyretin, which is carrier for the thyroid hormone thyroxine, and is also involved in retinol transport.…”
Section: Discussionmentioning
confidence: 99%
“…For example, apolipoproteins were found to be over-expressed in the milk of allergic mothers. Like protease inhibitors, apolipoproteins have been previously linked to asthma and atopy in children [ 28 ]; and more recently, their mimetic peptides have emerged as a potential new treatment for asthma [ 29 ]. Furthermore, our study provides also novel proteins that are different between allergic and non-allergic mothers, like transthyretin, which is carrier for the thyroid hormone thyroxine, and is also involved in retinol transport.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro and in vivo models have shown major proteins of HDL, apoA‐I and apoA‐II, as well as other proteins such as paraoxonase that co‐transport with HDL to have antioxidant properties and direct anti‐inflammatory roles through inhibition of the expression of adhesion molecules in various tissues including the lung . In contrast, an epidemiological study among schoolchildren has demonstrated a positive association between plasma apolipoprotein A and asthma outcomes . However, more recent reports on experimental animal asthma models have documented that apolipoprotein A‐I mimetic peptides attenuate the induction of asthma and decrease airway hyperresponsiveness, inflammation and oxidative stress .…”
Section: Discussionmentioning
confidence: 99%
“…A recent study in children with asthma has shown that higher LDL-cholesterol levels were associated with asthma occurrence and this association was amplified by overweight and obesity [6]. This finding is inconsistent with the earlier data indicating no association of apoB concentration with symptoms of asthma or allergy [7]. Having these controversies in mind, we aimed to elucidate whether there was an association between vitamin D status and lipid profile components and apolipoprotein B in a sample of children with newly diagnosed atopic asthma.…”
Section: Introductionmentioning
confidence: 72%